Distributed control for a modular multilevel converter - Yang, Shunfeng (2019)
Conventional centralized control strategies may reduce the flexibility and expandability of a modular multilevel converter (MMC) system. To tackle this issue, this paper proposes a distributed control architecture that is capable of assigning certain control tasks to distributed local controllers and improves the modularity of an MMC system. A central controller dealing with the output current regulation based on sensed arm currents is adopted. The control of MMC internal dynamics and the pulsewidth modulation (PWM) generation are distributed into local controllers. Unlike the conventional MMC control that needs all submodule capacitor voltages for capacitor voltage averaging, the proposed capacitor voltage control only relies on local submodule voltage measurement. Consequently, communication-intensive capacitor voltage transmission in each control cycle is not required and the communication burden of the control system can be significantly reduced. The control loops and possible control conflicts among submodules are presented and considered for system stability analysis. The effectiveness of the proposed distributed control architecture and capacitor voltage control for an MMC are confirmed by the start-up, steady state, and transient experimental results.